Communication for Participation of Worship Dancers for Thao Suranaree, Nakhon Ratchasima Province - Nirantechaphat, Wachirarat (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2024)
The Thao Suranari worship dance is an important activity of Nakhon Ratchasima Province to honor Thao Suranari's heroic deeds. This article is part of the research on “Studying the communication network of worship dancers for Thao Suranaree, Nakhon Ratchasima Province”. This is qualitative research, that aims to study communication for the participation of worship dancers. The results showed that the model of communication is as follows: The messenger (Sender) is the dancing lady of Thao Suranaree. Content (Message) is lyrics, dance moves, melodies, and music. Media (Channel/Media) is a dance to worship Thao Suranaree. And receivers are members who attend the ceremony. The communication process consists of three steps as follows: 1) The planning stage with all relevant parties to prepare for worship dances held annually on Victory Day celebrations from March 23 to April 3. 2) The dance practice stage may be practiced in one's own community or practiced in a centralized location and time by planning a trip with a group of friends or separately to rehearse as convenient. And 3) in the inspection and evaluation stage, each year's dance rehearsal has been adjusted to dance moves, lyrics, locations, and dance schedules as appropriate for the situation.